Abundance and Diversity of Floral Visitors on Jamun (Syzygium cumini L. Skeels) - G, Eswarappa; Somashekar, R K; B, Gagan (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The reproductive output in the form of seeds is dependent on pollinating species and the rate of effective pollination. In view of this fact the study on “Abundance and diversity of floral visitors on Jamun (Syzygium cumini L. Skeels) was carried out at Regional Horticultural Research and Extension Centre, College of Horticulture (RHREC); UHS sub campus, GKVK, Bengaluru-560 065. Totally thirty-one species of floral visitors were recorded on the wild and cultivated varieties of S. cumini, among them twelve were Hymenopterans (39%), six were Dipterans (19%), five were Lepidopterans (16%), seven were Coleopterans (23%) and one species belonged to Hemiptera (3%). Among the honey bees that visited the flowers, the per cent abundance of A. dorsata was highest followed by A. florea, A. cerana and T. iridipennis and they constituted 69.00 to 72.39 per cent of floral visitors. The per cent composition of ants that visited the flowers was highest, followed by Dipterans, Lepidopterans and Coleopterans and they together constituted 27.00 to 31.00 per cent. The diversity (H) of floral visitors varied throughout the day during 100 per cent flowering stage on all the wild and cultivated varieties of S. cumini. The peakactivity of honeybees, including other floral visitors was observed during morning hours on all wild and cultivated varieties of S. cumini. Among the floral visitors, the dominance (d) and diversity of honey bees was comparatively highest.